Are Basic Substances a Key to Sustainable Pest and Disease Management in Agriculture? An Open Field Perspective - Silvia Laura Toffolatti; Yann Davillerd; Ilaria D’Isita; Chiara Facchinelli; Giacinto Salvatore Germinara; Antonio Ippolito; Youssef Khamis; Jolanta Kowalska; Giuliana Maddalena; Patrice Marchand; Demetrio Marcianò; Kata Mihály; et al. (Plants, 2023)
Pathogens and pests constantly challenge food security and safety worldwide. The use of plant protection products to manage them raises concerns related to human health, the environment, and economic costs. Basic substances are active, non-toxic compounds that are not predominantly used as plant protection products but hold potential in crop protection. Basic substances’ attention is rising due to their safety and cost-effectiveness. However, data on their protection levels in crop protection strategies are lacking. In this review, we critically analyzed the literature concerning the field application of known and potential basic substances for managing diseases and pests, investigating their efficacy and potential integration into plant protection programs. Case studies related to grapevine, potato, and fruit protection from pre- and post-harvest diseases and pests were considered. In specific cases, basic substances and chitosan in particular, could complement or even substitute plant protection products, either chemicals or biologicals, but their efficacy varied greatly according to various factors, including the origin of the substance, the crop, the pathogen or pest, and the timing and method of application. Therefore, a careful evaluation of the field application is needed to promote the successful use of basic substances in sustainable pest management strategies in specific contexts.